Winter cover crops grown in low altitude condition - Emilso Damm dos Santos; Diego Nicolau Follmann; Onássis Deivis Schlösser; Anderson Crestani Pereira; Alessandro Dal ´´Col l Lucio; Estéfano Antonio Moresco (Semina: Ciências Agrárias, 2024)
The purpose of the study was to evaluate dry matter phytomass production, percentage of soil cover, and dry matter phytomass decomposition curve of cover crops in single and mix cultivation, in a low-altitude subtropical environment. The study was conducted in Santa Maria - RS, in agricultural years 2019/2020 and 2021/2022. The experimental design used was randomized blocks, with ten treatments and four replications. The experiments were conducted with four winter cover crops: White oat (WO), black oat (BO), forage turnip (FT), and common vetch (CV), in single cultivation and as a mix of cover plants. For the total production of dry matter phytomass, the FT and BO+CV+FT treatments stand out which present the highest averages between the experimental years, with values ​​4365.32 and 4109.87 kg ha-1. FT in single cultivation has a high potential for soil coverage in periods of 45 DAS, and the common vetch crop showed greater soil coverage in the late period, with 84% coverage at 90 days after sowing. The BO and WO treatments showed greater maintenance of dry phytomass in soil cover at the end of the 150-day period, presenting values greater than 40% of the initial volume of dry phytomass present in the production system. Recommending the exclusive cultivation of the species that meets the rural producer's objective.